2016
DOI: 10.1002/we.2027
|View full text |Cite
|
Sign up to set email alerts
|

Rotor‐tower interactions of DTU 10MW reference wind turbine with a non‐linear harmonic method

Abstract: In this paper, a computational study of the DTU 10MW reference wind turbine unsteady aerodynamics is presented. The whole wind turbine assembly was considered, including the complete rotor and the tower. The FINE/Turbo flow solver developed by NUMECA International was employed for the simulations. In particular, the Non‐Linear Harmonic (NLH) method was applied in order to accurately model flow unsteadiness at reduced computational cost. Important vortex shedding structures were identified at low blade span ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In previous analysis of Geometry 2 (Zahle et al, 2014), a region of three-dimensional flow radially pumped from the root to r 0 /R = 0.36 was observed. Moreover, a separation bubble is also present from the root to almost r 0 /R = 0.40 (Horcas et al, 2017). These factors increase the flow three-dimensionality at the inner radial part of the blade, making it more difficult for the quasithree-dimensional BL model to capture the flow features correctly.…”
Section: Spanwise Edge Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…In previous analysis of Geometry 2 (Zahle et al, 2014), a region of three-dimensional flow radially pumped from the root to r 0 /R = 0.36 was observed. Moreover, a separation bubble is also present from the root to almost r 0 /R = 0.40 (Horcas et al, 2017). These factors increase the flow three-dimensionality at the inner radial part of the blade, making it more difficult for the quasithree-dimensional BL model to capture the flow features correctly.…”
Section: Spanwise Edge Velocitymentioning
confidence: 99%
“…DNSs aim at exactly resolving the flow field, and they can thus provide detailed information about velocity fluctuations within the boundary layer, based on which results about transition and turbulence characteristics can be derived. At this moment, only a few studies of the transition process on wind-turbine blades using highresolution simulations are available (Jing et al, 2020). The DNS approach for transition prediction provides accurate results, but it implies a high computational cost.…”
Section: Introductionmentioning
confidence: 99%
“…Rahmati et al [21][22] also developed a nonlinear frequency domain method for the multi-row aeromechanical analysis of turbomachines and showed that a fully coupled multi-row configuration should be considered rather than a simplified isolated one to produce better accuracy in predicting flutter behaviour of the blades. Despite the fact that the frequency domain methods are typically used in turbomachinery analysis, there are only a few recently conducted studies in the field of wind turbine research which employ such methods [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Although the aerodynamic knowledge achieved in the past decades has contributed greatly to increase the performance and efficiency of wind turbine rotors, it is evident that increasing the power efficiency is still a major task for designers of modern wind turbines. The success of the aerodynamic progress is best illustrated by the change in rotor design from the relatively over-dimensioned kW size turbines in the 1980's [1] to the slender MW size turbines developed in recent years [2], [3], [4]. An evaluation of the wind power planning in Denmark showed that there is clearly a tendency to exclude smaller turbines in future design developments [5].…”
Section: Introductionmentioning
confidence: 99%